Secondary necrosis following caspase-activation can occur independently of gasdermin E - Gavali, Shubhangi; Maremonti, Francesca; Tonnus, Wulf; Gembardt, Florian; Nastassja Schlecht, Marlena; Flade, Karolin; von Mässenhausen, Anne; Tait, Stephen W. G.; Bornstein, Stefan R.; Linkermann, Andreas Günter (Advanced science, 2025)
Regulated necrosis is a known direct consequence of activation of the necroptosis- and pyroptosis- pathways, but may also result from apoptosis in a process referred to as secondary necrosis. Apoptosis is well understood to be mediated by caspase activation, but the mechanisms that lead to plasma membrane rupture in secondary necrosis remain considerably obscure. Recent data suggested a caspase-mediated cleavage of gasdermin E (GSDME), a member of the gasdermin family. Here, apoptosis induced by diphtheria toxin (DT) is employed as a novel tool to study secondary necrosis. In addition, cisplatin and anti-Fas monoclonal antibody Jo2 are employed to study secondary necrosis in cell culture and in vivo, respectively. Despite prominent, yet epiphenomenal cleavage of GSDME, it is demonstrated that silencing or CRISPR/Cas9-mediated knockout of GSDME does not compromise the kinetics of secondary necrosis induced by DT or cisplatin. During Jo2-induced acute liver toxicity in mice, GSDME expressed in the necrotic liver is detected predominantly in its uncleaved form. In conclusion, the hypothesis of GSDME to be a central mediator of secondary necrosis in these model systems is disproved.
Erstmals veröffentlicht: 4. November 2025
Gesehen am 24.11.2025